Dental Disease Outcomes Following a 2-Year Oral Health Promotion Program for Australian Aboriginal Children and Their Families: A 2-Arm Parallel, Single-blind, Randomised Controlled TrialResearch in Context - Lisa Jamieson; Lisa Smithers; Joanne Hedges; Eleanor Parker; Helen Mills; Kostas Kapellas; Herenia P. Lawrence; John R. Broughton; Xiangqun Ju (EClinicalMedicine, 2018)
Background: Dental disease has far-reaching impacts on child health and wellbeing. We worked with Aboriginal Australian communities to develop a multifaceted oral health promotion initiative to reduce children's experience of dental disease at age 2 years. Methods: This was a single-blind, parallel-arm, randomised controlled trial. Participants were recruited from health service providers across South Australia. Women pregnant with an Aboriginal child were eligible. The intervention comprised: (1) provision of dental care to mothers during pregnancy; (2) application of fluoride varnish to teeth of children at ages 6, 12 and 18 months; (3) motivational interviewing delivered in conjunction with; (4) anticipatory guidance. The primary outcome was untreated dental decay as assessed by the number of teeth with cavitated and non-cavitated carious lesions (mean dt) at child age 24 months. Analyses followed intention-to-treat principles. The RCT was registered with the Australian and New Zealand Clinical Trial Registry, ACTRN12611000111976. Findings: Women (n = 448) were recruited from February 2011 to May 2012, resulting in 223 children in the treatment group and 225 in the control. Mean dt at age two years was 0.62 (95% CI 0.59 to 0.65) for the intervention group and 0.89 (95% CI 0.85 to 0.92) for the control group (mean difference −0.27 (95% CI −0.31, −0.22)). Interpretation: A culturally-appropriate intervention at four time-points from pregnancy through to 18-months resulted in improvements in the oral health of Aboriginal children. Further consultation with Aboriginal communities is essential for understanding how to best sustain these oral health improvements for young Aboriginal children. Keywords: Early childhood caries, Aboriginal, Randomised controlled trial, Oral health promotion